JOB SATISFACTION OF PRIVATE SECTOR BANK’SEXECUTIVES IN BANGLADESH: A FACTOR ANALYSIS - Nimalathasan, B. (My University, 2012)
The present study has been attempted to understand and explain the job satisfaction, which influenced by utilitarian reasons (e.g., to increase productivity and organizational commitment, lower absenteeism and turnover, and ultimately increase organizational effectiveness) as well as humanitarian interests (i.e., the notion that employees deserve to be treated with respect and have their psychological and physical well-being maximized). The satisfied workers also tend to engage in Organizational Citizenship Behaviour (OCB) i.e., altruistic behaviours that exceed the formal requirements of a job. Dissatisfied workers show an increased propensity for counterproductive behaviours, including withdrawal, burnout, and workplace aggression. The present study emphasized on job satisfaction of private sector bank’s executives in Bangladesh. For primary data some bank executives have been selected purposively in Chittagong, Bangladesh with the sample size of thirty five. We used sophisticated statistical model Principal Component Analysis (PCA). The study has identified eight factors based on factor loadi ngs named as ‘better working environment’; officer’s view’;‘worked efficiently’; ‘present work’; ‘improving interpersonal relationship’; ‘bank treatments’; ‘colleagues’ and ‘challenging work’. However only ‘colleagues’ factor is significantly correlate with overall job satisfaction of bank executives